A quantitative comparison of the Howiesons Poort lithic assemblage from Kathu Pan 6 in the Northern Cape with other Howiesons Poort assemblages in Southern Africa - Matlhoko, Khumo (Department of Archaeology, 2025)
Howiesons Poort (HP) lithic assemblages have sparked many debates around their significance It is now widely accepted that the HP forms part of the Middle Stone Age, stratified above the Still Bay (SB) and/or beneath MSA III assemblages, however, reasons for the appearance and disappearance of the HP is still up for debate, and little work has been done to characterize its variability across geographic space. In my research I quantitatively compare data from published HP assemblages found in various coastal rock and cave sites in southern Africa to the HP sequence found in Kathu Pan 6 (KP6), an inland open-air site in the Northern Cape. The results of this quantitative analysis between KP6 and other sites, namely Klipdrift Shelter, Klasies River Mouth, and Pinnacle Point 5-6, will allow me to characterize geographical variability in the HP and identify possible explanations for this variability, including different foraging and mobility strategies in different environments across southern Africa.